Maximization of furanic compounds formation by dehydration and hydrogenation of xylose in one step over SO3-H functionalized H-beta catalyst in alcohol media - Gupta, Anshita; Nandanwar, Sachin U.; Niphadkar, Prashant; Simakova, Irina; Bokade, Vijay (Biomass & Bioenergy, 2020)
Furanic compounds such as furfural (FUR); furfuryl alcohol (F. Alc) are important renewable platform chemicals can be used as such or further convert for preparation of other value added products such as Levulinic acid (LA), Alkyl Levulinates, 2-Methyltetrahydrofuran (MTHF), and Tetrahydrofuran (THF) etc. Sulfonated H-beta zeolite was successfully prepared and used for the synthesis of furanic compounds especially FUR and F. Alc from c-xylose in one step using isopropanol as alcohol media. Prepared catalyst was well characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), BET, NH3-Temperature programmed desorption (TPD) and carbon-hydrogen-nitrogen-sulfur analysis (CHNS). It was found the total acid amount was increased with increase in sulfur loading which confirmed the sulfonic acid group (SO3-H) was successfully grafted onto zeolite structure. 3 wt% H-beta-SO3-H catalyst with optimized reaction parameters of 150 degrees C, 7 h, 25 wt% catalyst loading was tuned to get the highest furanic compound yield of 88.5% (FUR 76.8% + F.Alc 11.7%).The reusability study confirmed that there was a marginal drop of similar to 25% after 3 recycle runs.
Keywords: furfural; Furfuryl alcohol; H-beta; isopropanol; sulfonated zeolite; Xylose

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-beta zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
The sulfonated H-beta zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) fromD-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N-2 physisorption, NH3-temperature programmed desorption and carbon-hydrogen-nitrogen-sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-beta (S-beta) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-beta catalyst at 160 degrees C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-beta; HMF; levulinic acid; sulfonated zeolite; yield

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-β zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
Abstract The sulfonated H-β zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) from D-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N2 physisorption, NH3-temperature programmed desorption and carbon–hydrogen–nitrogen–sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-β (S-β) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-β catalyst at 160°C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-β; HMF; levulinic acid; sulfonated zeolite; yield

Methanol-to-light olefins reaction using Zn-Ag modified SSZ-13 catalyst - Dange, Rutvija M.; Gawali, Chirag B.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
The 2 wt.% of Zn and Ag (Zn1-x-Ag-x; x=0.2, 0.4, 0.6 %) modified SSZ-13 (SZ-13) zeolite was prepared by wet-impregnation method, and its catalytic activity was demonstrated for methanol-to-olefin (MTO). The Zn-0.6-Ag-0.4/SZ-13 catalyst exhibited high catalytic activity due to change in properties of catalyst. The Zn particles were highly dispersed inside the SZ-13; while Ag particles were dispersed on the surface of SZ-13, confirmed by HRTEM and surface area. The small % of Ag over SZ-13 promotes ethylene production via aromatization of reaction, and highly dispersed Zn on SZ-13 help to produce stable ethylene and propylene. The Zn-0.6-Ag-0.4/SZ-13 catalyst showed (similar to 10 %) higher light olefin (87 %) selectivity than parent SZ-13 as well as mono metal incorporated SZ-13. The higher catalytic activity was attributed due to effect of both metals (Zn and Ag), where Ag promotes partial aromatization on the surface, and Zn increases the Lewis acidity in the zeolite pore. This catalyst can help to improve the selectivity of light olefin using MTO reaction.
Keywords: Ethylene; Methanol-to-Olef; Propyl; Silver; SSZ; zinc